The Effectiveness of Acupressure in Reducing Pain After Coronary Angiography: a Systematic Review - Elvi Kurnia Damayanti; Asroful Hulam Zamroni; Johanes Eban B. Dorman; Rizki Nur Azhadin; Ninuk Dian Kurniawati (Universitas Pahlawan Tuanku Tambusai, 2025)
Coronary angiography, a critical diagnostic tool for coronary artery disease, often results in post-procedural pain that affects patient recovery and satisfaction. Acupressure, a non-invasive technique rooted in traditional Chinese medicine, has shown promise in reducing pain by stimulating endorphin release and enhancing physiological responses. This systematic review aimed to evaluate the effectiveness of acupressure in managing pain among patients undergoing coronary angiography. Four databases (Scopus, PubMed, ProQuest, and ScienceDirect) were searched for relevant articles published between 2020 and 2025, using keywords such as